Negotiating Education in an Immigration Context: Qualitative Insights into Age–Grade Mismatch and Family Cultural Capital - Zhang, Fengyi (Journal of Qualitative Research in Education, 2026)
This qualitative study explores how immigrant families experience and negotiate age–grade mismatch during school enrolment and transition, and how family cultural capital shapes their ability to engage with school placement decisions. Age grade mismatch (i.e., being below age grade level) can be considered as either a technical or guardian move, but has significant social, emotional, and educational implications. The research is based on semi-structured interviews with 12 immigrant parents and young people regarding the announcement, justification, and reaction to the placement decision-making in the daily interactions of the family and school, the results of which indicate that age–grade incompatibility is widely perceived as an institutional evaluation instead of an objective adaptation, which shapes the sense of belonging, confidence, and peer relationships in children. The ability of families to challenge or make new deals on the placement decisions differed significantly and was largely connected to access to information, language assistance, social networking, and knowledge of school systems. Some families could mobilise these resources to bring about change, but in other cases, the process appeared to be fixed and intimidating. The research points to the ability of language-based tests to blur the previous education and the support systems to propagate inequalities in situations where there are no established ways of review.